N-Bromo-(4-methylphenyl) Sulfonimide: A Mild and Efficient Reagent for Oxidative Deoximation of Oximes Under Microwave Irradiations - Amini Manesh, Abbas; Khazaei, Ardeshir (Asian Journal of Chemistry, 2010)
Aldoximes and ketoximes are converted to the parent carbonyl compounds in good yields when treated with N-bromo-(4-methylphenyl) sulfonimide (2), under microwave irradiations. The simple work-up minimizes the loss of product and oximes have been selectively oxidized in the presence of alcohols and alkenes.